Mechanisms Underlying Aquaporin-4 Subcellular Mislocalization in Epilepsy - Szu, Jenny I.; Binder, Devin K. (Frontiers in Cellular Neuroscience, 2022)
Epilepsy is a chronic brain disorder characterized by unprovoked seizures. Mechanisms underlying seizure activity have been intensely investigated. Alterations in astrocytic channels and transporters have shown to be a critical player in seizure generation and epileptogenesis. One key protein involved in such processes is the astrocyte water channel aquaporin-4 (AQP4). Studies have revealed that perivascular AQP4 redistributes away from astrocyte endfeet and towards the neuropil in both clinical and preclinical studies. This subcellular mislocalization significantly impacts neuronal hyperexcitability and understanding how AQP4 becomes dysregulated in epilepsy is beginning to emerge. In this review, we evaluate the role of AQP4 dysregulation and mislocalization in epilepsy.